Optimal Sizing of a Standalone Photovoltaic (PV) System for Residential Customers Considering Electricity Consumption Patterns: A Case Study of Ibadan City, Nigeria - Egbon, Onyeka Collins (Auckland University of Technology, 2019)
With the regular electricity outages and the growing demand for electricity in Nigeria, households are now depending heavily on generators powered by fossil fuels such as diesel and gasoline as their major source of electricity. Solar energy has been identified as a good alternative to meet the country’s growing demand. However, the stochastic nature of electricity consumption among different households makes it complicated to select an optimal system size. This study investigates the appliance-related factors that contribute to the increasing rate of residential electricity consumption in Nigeria and selection of an optimal system for different sociodemographic groups. In this location, where electricity consumption data is unavailable, a questionnaire survey was employed to closely predict the electricity consumption patterns of low-, middle- and high-income households in Ibadan city, Nigeria and a residential load profile was created. The study results show that incandescent bulbs, which inherently have a higher rate of electricity consumption than energy-saving bulbs, are still being used in almost every household in the city. Also, low-income households own more electric fans than households in the high-income group, and households in the high-income group own more air conditioners. The methodology employed in this study enabled the realistic prediction of stochastic household electrical load which influences the optimal sizing of a standalone photovoltaic system (SAPVS) as an alternative source of electricity. The system advisor model (SAM) software was then used to simulate the proposed system performance to determine its feasibility, based on economic criteria such as levelised cost of energy (LCOE). Results show that, taking the electricity consumption pattern into consideration, an optimally sized SAPVS has a lower LCOE than diesel and gasoline generators.
Keywords: Solar; Standalone PV; Realiability; Economic analysis; Solar potential; PV